PENINGKATAN KEMAMPUAN BERPIKIR KRITIS SISWA MELALUI PENERAPAN METODE DEBAT DALAM PEMBELAJARAN PPKn MATERI POKOK KEBANGKITAN NASIONAL DI KELAS VIII-2 SMP NEGERI 3 TIGAPANAH TAHUN PELAJARAN 2018/2019 (JS (JURNAL SEKOLAH), 2021)
Abstract: The purpose of this study was to determine the improvement of critical thinking skills and student learning activities in Civics learning through the application of the debate learning method on the subject matter of national awakening in class VIII-2 SMP Negeri 3 Tigapanah in the 2018/2019 academic year. This classroom action research took place in two cycles. The research was conducted at SMP Negeri 3 Tigapanah from January 2019 to April 2019. The research subjects were all students of class VIII-2 SMP Negeri 3 Tigapanah in the 2018/2019 academic year, totaling 30 students. Data on critical thinking skills were obtained through formative tests while data on social attitudes were obtained through observation. The results showed; 1) the debate learning method succeeded in increasing students' critical thinking skills towards national awakening in Civics learning with scores in Formative I showing an average of 65 with 53% classical completeness and in Formative II showing an average of 79 with 87% classical completeness or an increase of 34 %; 2) the debate learning method succeeded in increasing student learning activities in Civics learning from Cycle I to Cycle II as indicated by the percentage of active students in Cycle I of 67% and in Cycle II of 87% with an increase of 20%.Keywords: Learning Activities, Critical Thinking, DebateAbstrak: Tujuan penelitian ini adalah untuk mengetahui peningkatan kemampuan berpikir kritis dan aktifitas belajar siswa dalam pembelajaran PPKn melalui penerapan metode pembelajaran debat pada materi pokok kebangkitan nasional di kelas VIII-2 SMP Negeri 3 Tigapanah tahun pelajaran 2018/2019. Penelitian tindakan kelas ini berlangsung dalam dua siklus. Penelitian dilaksanakan di SMP Negeri 3 Tigapanah pada bulan Januari 2019 sampai dengan bulan April 2019. Subjek penelitian adalah seluruh siswa kelas VIII-2 SMP Negeri 3 Tigapanah tahun pelajaran 2018/2019 yang berjumlah 30 siswa. Data kemampuan berpikir kritis diperoleh melalui tes formatif sedangkan data sikap sosial diperoleh melalui observasi. Hasil penelitian menunjukan; 1) metode pembelajaran debat berhasil meningkatkan kemampuan berpikir kritis siswa terhadap kebangkitan nasional dalam pembelajaran PPKn dengan nilai pada Formatif I menunjukkan rata-rata 65 dengan ketuntasan kalsikal 53% dan pada Formatif II menunjukkan rata-rata 79 dengan ketuntasan klasikal 87% atau terjadi peningkatan 34%; 2) metode pembelajaran debat berhasil meningkatkan aktifitas belajar siswa dalam pembelajaran PPKn dari Siklus I ke Siklus II ditunjukkan dengan persentase siswa aktif Siklus I sebesar 67% dan pada Siklus II sebesar 87% dengan peningkatan 20%.Kata Kunci: Aktifitas Belajar, Berpikir Kritis, Debat